REVOLUTIONIZING USER EXPERIENCE: ARCHITECTURAL INNOVATIONS IN OVO PAYMENT APPLICATION - Yani, Mega Fitri; Muhammad, Hasan Abdullah; Agustiana, Nathifa; Asriana, Asriana; Sandy, Muhammad Dwi Hary; Lubis, Muharman (STKIP PGRI Tulungagung, 2024)
In the era of digital transformation, mobile-based payment applications have become an important element in everyday life, changing the way transactions and managing finances. Online payment applications provide significant benefits by making financial transactions easier without cash, providing flexibility in choosing brands, and supporting the progress of fintech businesses and startups in the digital financial sector. Lippo Group, through OVO, presents innovation in electronic money payment systems. OVO's rapid growth lies not only in the ease of financial transactions, but also in its mobile application which is designed to provide a better user experience. This research analyzes architectural innovation in the OVO mobile application, aiming to revolutionize the user experience and increase OVO's competitiveness in the mobile payments industry. Using descriptive qualitative methods, this research utilizes user cards, storyboards, and customer journeys to analyze the implementation of Microservices Architecture and Load Balancing. The results show that this innovation provides significant benefits, improving the system's scalability, reliability and maintenance efficiency. Using Load Balancing is effective in solving balance problems and customer service response. This research provides in-depth insight into the evolution of financial applications in Indonesia.